2021
DOI: 10.1186/s12868-021-00667-8
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral ventriculomegaly in myotonic dystrophy type 1: normal pressure hydrocephalus-like appearances on magnetic resonance imaging

Abstract: Background Cerebral ventriculomegaly is an abnormal feature characteristic of myotonic dystrophy type 1 (DM1). This retrospective study investigated the morphologic changes accompanied by ventriculomegaly in DM1 on brain MRI. Methods One hundred and twelve adult patients with DM1 and 50 sex- and age-matched controls were assessed. The imaging characteristics for evaluations included the z-Evans Index (ventriculomegaly), callosal angle (CA), enlarge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In elderly DM1 group, prevalence of DESH was 21% and the z-Evans index [12], an improved version of the Evans index, increased with age [11]. Notably, there was no significant difference in average callosal angle between DM1 and age-matched control (DM1 and control; 123° vs. 123°) [11].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In elderly DM1 group, prevalence of DESH was 21% and the z-Evans index [12], an improved version of the Evans index, increased with age [11]. Notably, there was no significant difference in average callosal angle between DM1 and age-matched control (DM1 and control; 123° vs. 123°) [11].…”
Section: Discussionmentioning
confidence: 87%
“…In the brain imaging of DM1, several findings are reported including whole-brain atrophy, increased ventricular volume, widespread volume reduction of cortical and deep gray matter and reduced cortical thickness (occipital, parietal and temporal lobes) [ 10 ]. Additionally, an MRI study of 112 patients with DM1 revealed that NPH-like appearances including enlarged ventricles and DESH are frequent signs in DM1 over 50 years old [ 11 ]. In elderly DM1 group, prevalence of DESH was 21% and the z-Evans index [ 12 ], an improved version of the Evans index, increased with age [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain involvement in DM1 includes the presence of hyperostosis and whole brain atrophy, mostly evaluated in group analysis using advanced brain MRI techniques [ 5 ], and subcortical atrophy in form of increased ventricular volume that rarely can result in a severe cerebral ventriculomegaly with a normal pressure hydrocephalus-like appearance on MR imaging [ 6 ].…”
Section: Introductionmentioning
confidence: 99%